PERINATAL OUTCOME IN PATIENTS WITH PRE-ECLAMPSIA AT THE UNIVERSITY OF MAIDUGURI TEACHING HOSPITAL, NIGERIA - GEIDAM AD; BAKO B; KULLIMA AA; KAWUWA MB; KADAS AS (Ntec Specialist, 2008)
Background: Pre-eclampsia, a common maternal disease in pregnancy is an important cause of perinatal morbidity and mortality especially in developing countries. Objectives: To determine the perinatal outcome of patients with pre-eclampsia in our environment. Methods: A retrospective review of the perinatal outcome of patients with pre-eclampsia managed at the University of Maiduguri Teaching Hospital from January 2005 to June 2007. Logistic regression analysis was used to determine sociodemographic and obstetrics factors that are independently associated with perinatal mortality in these patients. Results: During the study period, there were 84 cases of preeclampsia and 3,560 deliveries giving a pre-eclampsia prevalence of 2.36%. Sixty-nine cases (82.1%) were available for review. The mean booking diastolic blood pressure of the study group was 78.6±15.7 mmHg. Majority of the patients 55(79.7%) were in the age group 19-35 years and 33(47.8%) were primigravidae. In 36(52.2%) of the cases, the birth weight of the babies was less tahn 2.5 Kg and IUGR was diagnosed in 37(53.6%). There were 16 perinatal death giving a perinatal mortality rate of 262/1000 live birth. IUGR (OR=11.35, 95%CI=2.06-62.55, p=0.005) and diagnosis of PE at a gestational age less than 32 weeks (OR=3.39, 95%CI=1.09-10.55, p=0.04) were found to be independently associated with perinatal mortality in patients with preeclampsia. Conclusion: Pre-eclampsia is associated with adverse perinatal outcome, with early onset disease and IUGR being independently associated with an increase risk of perinatal mortality